Laparoscopic fluorescence navigation for left-sided colon and rectal cancer: Blood flow evaluation, vessel and ureteral navigation, clip marking and trans-anal tube insertion. (December 2020) - Ryu, Shunjin; Ishida, Kota; Okamoto, Atsuko; Nakashima, Keigo; Hara, Keigo; Ito, Ryusuke; Nakabayashi, Yukio
Abstract: Background: Recently, the indocyanine green (ICG) fluorescence navigation method has attracted much attention as a means of intraoperative navigation, especially during laparoscopic surgery. The newly developed near-infrared (NIR) fluorescent resin also emits NIR fluorescence, as does ICG. Presently, new devices made with this resin are being developed. The purpose of this study was to present our fluorescence navigation techniques for left-sided colon and rectal cancer. Method: Fifty-nine patients with left-sided colon and rectal cancer underwent laparoscopic surgery with fluorescence navigation between July 2019 and April 2020. The surgeries included 54 intestinal blood flow (IBF) evaluations using ICG, 16 preoperative fluorescence clip marking (FCM) procedures, 7 fluorescence ureteral navigation procedures, 4 fluorescence vessel navigation (FVN) procedures during lateral lymph node dissection, and 3 fluorescence-guided trans -anal tube insertion procedures. Laparoscopic surgery and fluorescence observation were performed using a VISERA ELITE 2. In FCM, the Zeoclip FS device was used. In ureteral navigation and trans -anal tube insertion, the Near-Infrared Ray Catheter (NIRC™) fluorescent ureteral catheter (NIRFUC) was used. Results: No complications related to the fluorescence navigation techniques, including those involving ICG, the Zeoclip FS and the NIRFUC, occurred. In 5 cases, the surgical plan was changed according to the IBF evaluation with ICG, and no anastomotic leakage occurred in those cases. These fluorescence navigation techniques provide previously unavailable visual information regarding the IBF, vessel and ureter routes and accurate endoscopic clip and drainage tube locations in the intestinal tract. Conclusions: Technology to visualize blood flow dynamics and structures using fluorescence can be considered innovative, especially when applied in laparoscopic surgery, which relies on vision. The popularity of fluorescence navigation has also appeared to increase the safety of colorectal surgery. Clinical trial registration: Examination of fluorescence navigation for laparoscopic colorectal cancer surgery. Research Ethics Committee of the Kawaguchi Municipal Medical Center (Saitama, Japan) approval number: 2020-3. https://kawaguchi-mmc.org/wp-content/uploads/clinicalresearch-r02.pdf . Highlights: Fluorescence clip marking is a new marking technique for delineation of tumour. Fluorescence ureteral navigation enables clear identification of the ureter. Fluorescence-guided trans -anal tube insertion is a safe method for anastomosis. ICG-fluorescence vessel navigation improves the ease and safety of surgery. Blood flow evaluations with ICG may improve the assessment of anastomosis.